ANALYSIS OF FINANCIAL STATEMENTS SMALL AND MEDIUM ENTERPRISES BASED ON SAK - ETAP - Pasaribu, Marsaulina P.L.; Suherman, Asep (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this study was to 1) find out the obstacles faced by the DRM Workshop in presenting financial reports, and 2) Assist the DRM Workshop in presenting financial reports based on SAK ETAP. The presentation of financial statements in a company is very important to do, because from these financial statements we can find out that our company is making a profit/loss. The research method used is descriptive analysis method, which is a writing method that utilizes qualitative data and is described descriptively, and the data used is primary data, because the data is obtained directly from the results of interviews with the DRM Workshop owner, namely in the form of information on the presentation of the DRM Workshop financial statements. The DRM workshop recording financial statements is still very simple, only limited to the total of expenses and income. The DRM workshop has not recorded financial statements in accordance with SAK ETAP. Constraints that affect the DRM Workshop have not implemented financial reports according to SAK ETAP, namely because of educational background, DRM Workshop considers financial reports to be less important, and there is still a mix of business and personal finances.